차세대 고등학교 경제교과서의 효과성 분석 : 경제과목 오개념을 중심으로 - 문명신, 최민식 (교과교육학연구, 2011)
본 연구는 7차 교육과정의 경제교과서의 오류를 보완하기 위해 기획적으로 만들어진 차세대 고등학교 경제교과서의 효과성을 분석하는 것을 목적으로 하였다. 전국연합학력평가의 사회탐구 영역에서 경제 과목 시험문항과 결과에 대한 분석을 통해 경제과목의 오개념을 추출하고 이를 중심으로 차세대 경제교과서와 기존 교과서를 비교분석하여 차세대 경제교과서가 학생들의 오개념 형성을 극복할 수 있는 대안적인 교과서가 될 수 있는지 평가하였다. 분석결과 차세대 경제교과서가 현행 경제교과서에 비해 오개념이 형성된 단원에 대한 설명을 학생들이 쉽게 접할 수 있는 사례들을 통해 구체적이며 자세하게 기술하고 있다는 것을 확인할 수 있었다. 또한 질적으로 실시된 교과서 비교분석 방법의 타당성을 재확인 하고 분석결과의 강건성(robustness)을 재확인하기 위해 실험분석을 실시하였다. 고등학교 1학년 학생을대상으로 실시한 실험 분석을 통해서도 차세대 경제교과서가 가장 핵심적인 경제원리의 하나인 기회비용을 설명하는데 더 효과적인 것으로 나타났다. 그러나 동일한 실험 분석에서 차세대 경제교과서는 또 하나의 경제 주요개념이며 효율적인 자원배분에 대한 시장의 한계성을 제공하는 외부성을 설명하는 데는 효과적이지 못한 것으로 나타났다. This study aims to evaluate effectiveness of an alternative high school economics textbook (Next-generation Economics Textbook: NGET) by focusing on how the new textbook effectively deals with the common economic misconceptions that are strongly held among students. We collected data on common economic misconceptions by using nation-wide tests in Korea that were administrated centrally by the Korea Institute for Curriculum and Evaluation (KICE). We also conducted an experiment to see if the different approaches adopted by the NGET would make any difference in the student learning process with respect to the two most common economic misconceptions: opportunity cost and externalities. The results indicate that the next-generation economics textbook presents more relevant and rich examples of economic principles and concepts than the other existing textbooks. Reading material and exploration activities in the next-generation economics textbook contain more interesting examples and reasonable activities to help students understand the economics concepts more clearly. The results from our experiment suggest that the NGET provides better learning material on opportunity costs. The NGET, however, fails to offer effective learning material for explaining the concept of externalities. This supports the criticism that the NGET relies heavily on the market-centered economic perspective to explain and seek answers to economic issues and problems. KCI Citation Count: 6